N, P and K fertilizer consumption status and cropping intensity in Murshidabad District, India - Fazlur Rahman,; Jannatul Ferdosh, (National Geographical Journal of India, 2022)
The present research was conducted to assess the status of N,P, K fertilizer consumption and cropping intensity for 17 years from 2000-01 to 2017-18. For this purpose, CAGR, Gibbs-Martin Index, MLR model, Karl Pearson correlation coefficient were employed. The result showed that (i) The consumption of nitrogen (N) fertilizer at 75,642 metric tonnes, P at 39,762 metric tonnes, and K at 33,875 metric tonnes during 2017-18 registered an increase of 2.19 percent, 2.20 percent, and 1.47 percent, respectively, over 2000-01, while cropping intensity ramped up from 223 (in 2000-01) to 245 (in 2017-18) percent with the increase of 0.55 percent. (ii) On an average, Khargram, Sagardighi, Murshidabad-Jiaganj, Nabagram, and Burwan were the highest NPK consumers, whereas Beldanga-I, Berhampore, Beldanga-II, Murshidabad-Jiaganj, and Lalgola were considered as highest C.I contributors. (iii) CFAI increased dramatically from 128.32 kg/ha to 152.68 kg/ha, with a geographical pattern showing high in the south-west and low in the south. (iv) In 2017-18, the N, P, K usage ratio were 2.23: 1.17: 1, relative to 1.88: 1.04: 1 in 2000-01. (v) Higher or lower use of N, P, K had no significant influence on cropping (agricultural) intensity. The analysis also pointed out that organic manure was being used by the farmers, and green manure crops like Dhaincha were progressively gaining popularity in the study area. Because of the unanticipated population growth, balanced consumption of fertilizers (N, P, K) and harvest intensity are crucial to boosting agricultural production, food security, and ecological sustainability.